Penggunaan Gaya Bahasa dalam Lirik Lagu Sal Priadi - Reza Aribimo Wicaksono (Studi Administrasi Publik dan ilmu Komunikasi, 2024)
Sal Priadi’s song lyrics are known for their rich and complex use of language, blending metaphors, symbolism, and allusion to create profound and meaningful works. This study aims to analyze how Sal Priadi uses language styles to enrich meaning, create emotional atmospheres, and enhance the listening experience. A qualitative analysis was conducted on several of Sal Priadi's songs, selected for their lyrical richness. The findings reveal that Sal Priadi successfully integrates poetic elements to convey universal themes like love, longing, and loss in a unique and deep manner. The use of complex language provides interpretive freedom for listeners, enhancing the aesthetic value of his songs, making them not only entertainment but also mini works of literature. Through this approach, Sal Priadi is recognized not only as a musician but also as an artist who harmoniously combines language and music, creating a deeper listening experience that resonates with audiences across generations.